2007
DOI: 10.1091/mbc.e07-05-0485
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase A and Sch9 Cooperatively Regulate Induction of Autophagy inSaccharomyces cerevisiae

Abstract: Autophagy is a highly conserved, degradative process in eukaryotic cells. The rapamycin-sensitive Tor kinase complex 1 (TORC1) has a major role in regulating induction of autophagy; however, the regulatory mechanisms are not fully understood. Here, we find that the protein kinase A (PKA) and Sch9 signaling pathways regulate autophagy cooperatively in yeast. Autophagy is induced in cells when PKA and Sch9 are simultaneously inactivated. Mutant alleles of these kinases bearing a mutation that confers sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
243
1
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 227 publications
(259 citation statements)
references
References 39 publications
(72 reference statements)
9
243
1
6
Order By: Relevance
“…For example, when cells are grown on acetate as the sole carbon source in conditions of nitrogen limitation, Rim15 promotes Ume6 phosphorylation and disrupts the association of Sin3 and Rpd3 with the complex, thus relieving transcriptional repression of the target genes (12). In addition, we have shown that Rim15 is a positive regulator of autophagy (17,18), although its relevant target(s) had not been identified. Therefore, we decided to investigate a potential role for Rim15 in Ume6-regulated Atg8 induction.…”
Section: Rim15 Promotes Ume6 Phosphorylation and Functions As A Positivementioning
confidence: 84%
See 1 more Smart Citation
“…For example, when cells are grown on acetate as the sole carbon source in conditions of nitrogen limitation, Rim15 promotes Ume6 phosphorylation and disrupts the association of Sin3 and Rpd3 with the complex, thus relieving transcriptional repression of the target genes (12). In addition, we have shown that Rim15 is a positive regulator of autophagy (17,18), although its relevant target(s) had not been identified. Therefore, we decided to investigate a potential role for Rim15 in Ume6-regulated Atg8 induction.…”
Section: Rim15 Promotes Ume6 Phosphorylation and Functions As A Positivementioning
confidence: 84%
“…Rim15 plays an important role in integrating many nutrient-regulatory signals and, therefore, plays a central role in regulating autophagy (17,22). Rim15 is negatively regulated through direct phosphorylation by cAMP-dependent protein kinase A (PKA) and Sch9 in the presence of glucose and nitrogen (23,24) and is involved in the autophagy induction that occurs upon PKA-Sch9 inactivation (18). PKA and Sch9 are upstream sensors that act to negatively regulate autophagy; however, the downstream components in this signaling pathway are unknown, and how PKA and Sch9 signaling affects the autophagy machinery to regulate autophagosome formation has not been elucidated previously.…”
Section: Discussionmentioning
confidence: 99%
“…Also Pho85-Pho80, which phosphorylates Rim15 at Thr 1075 , controls the nuclear export of Rim15. PDS post-diauxic shift, STRE stressresponsive element combined inactivation of Sch9 and PKA appeared to additively stimulate autophagy, indicating that also for autophagy Sch9 and PKA act, at least in part, in parallel to the TORC1 pathways (Yorimitsu et al 2007). …”
Section: The Protein Kinase Sch9mentioning
confidence: 98%
“…These studies revealed that autophagy is induced in yeast cells upon the simultaneous inactivation of Sch9 and PKA (Yorimitsu et al 2007). This induction required the Atg1 kinase complex and was only in part dependent on the presence of Rim15 and Msn2/4.…”
Section: The Protein Kinase Sch9mentioning
confidence: 99%
See 1 more Smart Citation